Hematological Characterizations and Molecular Diagnostic Aspects of Hb Wiangpapao [α44(CE2)Pro→Ser (α1), CCG>TCG; HBA1: c.133C>T], a New α-Globin Variant Found in a Pregnant Thai Woman - Sitthichai Panyasai (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. We report the hematological parameters and provide a rapid molecular analysis method for detection of Hb Wiangpapao [α44(CE2)Pro→Ser, CCG>TCG; HBA1: c.133C>T], a new α-globin variant found in a pregnant Thai woman. Her red cell indices were measured by an automated blood counter. The results were: red blood cell (RBC) count 4.03 × 1012/L, Hb 13.1 (g/dL), packed cell volume (PCV) 0.39 L/L, mean corpuscular volume (MCV) 97.0 fL, mean corpuscular hemoglobin (Hb) (MCH) 32.5 pg, mean corpuscular Hb concentration (MCHC) 33.4 g/dL, and RBC distribution width (RDW) 9.4%. The Hb typing by high performance liquid chromatography (HPLC) showed 13.6% abnormal Hb at a retention time of 2.20 min. that was difficult to distinguish from Hb A. On the capillary electrophoresis (CE) electropherogram, this hemoglobinopathy peak did not separate from the Hb A peak. DNA sequencing showed a C>T transition at the first position of codon 44 (CCG>TCG) of the α1-globin gene that led to a substitution of proline for serine. This mutation has not been recorded in the public databases. Therefore, we named it Hb Wiangpapao as it was first discovered in the Wiangpapao District, Chiang Rai, Thailand. The multiplex allele-specific polymerase chain reaction (ASPCR) for detection of Hb Wiangpapao was developed and revealed a 510 bp specifically amplified fragment. The better understanding of hematological characterizations and the newly developed multiplex ASPCR for diagnosis of Hb Wiangpapao are useful for genetic counseling and family education.